Teorema del texto agotado. - Pablos Coello, José Manuel de (Estudios sobre el Mensaje Periodístico, 2000)
Theorem of the finished text All journalistic text has an start and an end. The message concludes when all that forms its content has been said. The full stop will appear at the end of the message. So simple is 215 José Manuel de Pablos Coello Teorema del texto agotado this theorem. Nevertheless it is regrettably violated in numerous occasions. This article analizes "how and why" it happens. It examines concrete cases and establishes eight solutions in order to prevent the described situation from leading to a communication fail with the reader.